ANALISIS KESULITAN–KESULITAN YANG DIALAMI GURU EKONOMI UNTUK MELAKUKAN PENELITIAN TINDAKAN KELAS - Mayang Risqi Putriani; Sri Wahyuni; Leny Noviani (Department of Economics Education, Universitas Sebelas Maret, 2018)
This research was aimed to know (1) the reasons majority of economic teachers have not conduct Classroom Action Research (CAR), (2) the school’s efforts to encourage and overcome difficulties in conducting CAR. This research was a qualitative research which used case study methodology the techniques of collecting data were used unstructured planning interview and documentation with the techniques of data analysis used analysis interactive Miles and Huberman. The result of this research was following: First, the main reason was that they were not motivated yet while the supporting reasons were following: (a) facing technical difficulties; (b) teachers’ perceptions such as busy and CAR was burden teachers, time and financial consuming; (c) training of CAR wasn’t optimal, (d) lack of reading habit about books of CAR; (e) lack of experiences in research; (f) influence of teachers’ age. Although the age wasn’t fully influenced, there were other factors that influenced teachers in conducting CAR such as their experiences, motivation and manner toward rule. Second, the school’s efforts to encourage teacher in conducting CAR were by giving socialism, information and reminding importance CAR mainly when the meeting was held of school whereas the school’s efforts to overcome the teachers’ difficulties were by providing internet access and reference books of CAR.